(untitled) (Indian Journal of Fibre & Textile Research (IJFTR), 2024)
This study introduces a sustainable approach to generic denim fabric washing by employing immobilized cellulase on two eco-friendly polymers (chitosan and Eudragit S-100). The immobilization process enhances the stability and reusability of cellulase, while the choice of chitosan and Eudragit S-100 allows for reversible solubility and insolubility, providing easy removal of the enzyme after the washing process. The study investigates the enzymatic activity and stability of cellulase when immobilized on chitosan and Eudragit S-100 and assesses their efficiency in denim fading. The experimental results reveal that the immobilized cellulase exhibits some decreased activity with increased pH and thermal stability. The immobilized cellulase grades equivalent denim decolouration with reduced back-staining for three consecutive cycles in comparison to native cellulase which is drained after a single use. The proposed method not only addresses the economic constraints of the reusability of enzymes but also contributes to the development of innovative and sustainable practices in textile industry.